Numerical Analysis of Micromixer based on Microrobots - Yilmaz, Abdurrahim; Demircali, Ali Anil; Baban, Beste; Ozkasap, Serra; Samoylenko, Yegor; Chadha, Krishiv; Uvet, Huseyin (IEEE, 2021)
In this study, performances of a micromixer based on microfluidics are estimated numerically. Faster and more efficient an active micromixer model that minimizes human contact was presented by making numerical calculations with basic microfluidic equations. In the model that we created, two liquids of the same type were given to the micromixer environment based on microrobotic-shaped mixer with 0.005 second steps for the 3 seconds. The concentration of the first liquid was 1 mol/m3, and the concentration of the second liquid was 5 mol/m3. As a result of mixing, the new concentration of the mixed two liquids was expected to be 3 mol/m3 at ideal conditions. According to the value calculated as a result of the simulation, the concentration of the liquid was 2.945 mol/m3. The mixing efficiency obtained from the model examined in the study was 98.181%. In order to better interpret the efficiency of the presented model, it was compared with other active micromixer models.
Keywords: Microrobots; Micromixers; Numerical Analysis; MIXING PERFORMANCE; Cell Biology; Engineering